2022
DOI: 10.1016/j.resplu.2022.100208
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest: Does rurality decrease chances of survival?

Abstract: Background Geographical setting is seldomly taken into account when investigating out-of-hospital cardiac arrest (OHCA). It is a common notion that living in rural areas means a lower chance of fast and effective helpwhen suffering a time-critical event. This retrospective cohort study investigates this hypothesis and compares across healthcare-divided administrative regions. Methods We included only witnessed OHCAs to minimize the risk that outcome was predetermined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“… 28 However, another recent Danish study by Ringgren et al found increased EMS response time in rural areas but without any differences in 30‐day survival in witnessed OHCA. 9 Like Ringgren et al, we observed increased EMS response time in rural areas; yet, after adjusting for this, 30‐day survival was still significantly lower in rural areas compared with urban areas. The difference in 30‐day survival between the 2 studies (in a relatively similar cohort) might be explained by differences in categorization of urban and rural areas between the studies.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“… 28 However, another recent Danish study by Ringgren et al found increased EMS response time in rural areas but without any differences in 30‐day survival in witnessed OHCA. 9 Like Ringgren et al, we observed increased EMS response time in rural areas; yet, after adjusting for this, 30‐day survival was still significantly lower in rural areas compared with urban areas. The difference in 30‐day survival between the 2 studies (in a relatively similar cohort) might be explained by differences in categorization of urban and rural areas between the studies.…”
Section: Discussionsupporting
confidence: 72%
“…Of note, we used the standardized Degree of Urbanization Tool, as recommended by the European Commission, whereas Ringgren et al used a different categorization for urbanization. 9 It should be recognized that the observed EMS response times throughout the Danish regions are low when comparing with other countries. Even in rural parts of Denmark, the median EMS response time was 8 minutes, which is what other EMS agencies can provide in urban areas, and EMS response times have been associated with increased survival.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 24 , 43 , 44 Further, it was shown that rurality does not decrease the chance of survival from OHCA with a shockable rhythm in Denmark. 24 Similar to the disparities in the factors associated with survival from OHCA, many social disparities have been shown in the distribution of BLS education. It is known that people who have lower education and income levels, living in rural areas, and older age generally have lower BLS course participation rates.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study found that EMS response time was prolonged in OHCA, particularly in rural communities; however, there were no significant differences in 30-day survival when compared to early hospital arrival times. 4 This research identified several pre-existing comorbidities that predicted scene times greater than eight minutes. Adult trauma patients who had a diagnosis of alcohol use disorder, dementia, and personality disorders were more likely to have a scene time greater than eight minutes.…”
mentioning
confidence: 99%